Pengaruh Interaksi Motivasi Belajar pada Kemampuan Memecahkan Masalah dalam Pembelajaran IPS di SMPN 8 Cimahi - Ilham Muhamad Sya'ban; Hari Mulyadi; Sapriya Sapriya (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aimed to analyze the interaction between learning motivation and problem-solving skills in the context of Social Sciences (IPS) learning at SMPN 8 Cimahi. Adopting a quantitative approach through a 2^3 factorial experimental design, this research involved 60 students divided into an experimental group (using Problem-Based Learning - PBL) and a control group (using Inquiry Learning). Data was collected through observation, documentation, pretest-posttest, and questionnaires, then analyzed using descriptive and inferential statistics (One-Way ANOVA) with SPSS 26.0. The results showed a significant increase in problem-solving skills in the PBL group compared to the Inquiry group, especially due to the interaction with student learning motivation. Descriptively, the average normalized gain score of the PBL group (0.8424) was superior to that of the Inquiry group (0.7147). The One-Way ANOVA test confirmed significant differences in problem-solving skill improvement for both learning groups (PBL: F=44.220, sig<0.000; Inquiry: F=4.866, sig<0.016), with effects varying based on motivation levels. Furthermore, the interaction effect test (F=4.410, sig=0.022) confirmed a combined influence between learning methods and student motivation. These findings conclude that PBL is more effective in enhancing student engagement and problem-solving skills, while also emphasizing the importance of considering teaching methods and student motivation levels when designing learning activities.